2013
DOI: 10.1136/thoraxjnl-2013-204282
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for community-acquired pneumonia in adults in Europe: a literature review

Abstract: BackgroundCommunity-acquired pneumonia (CAP) causes considerable morbidity and mortality in adults, particularly in the elderly.MethodsStructured searches of PubMed were conducted to identify up-to-date information on the incidence of CAP in adults in Europe, as well as data on lifestyle and medical risk factors for CAP.ResultsThe overall annual incidence of CAP in adults ranged between 1.07 to 1.2 per 1000 person-years and 1.54 to 1.7 per 1000 population and increased with age (14 per 1000 person-years in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
458
2
27

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(526 citation statements)
references
References 82 publications
39
458
2
27
Order By: Relevance
“…10 Old age, underlying respiratory system disease, hypertension, hypercholesterolemia, heart disease, cerebral hemorrhage, cerebral infarction, stroke, diabetes mellitus, kidney disease, smoking, and low ADL status are associated with an increased risk of hospitalization due to pneumonia or influenza. 11 On the other hand, the vaccination rate typically is higher in healthy elderly than in weak elderly. Pneumococcus is cited as the major pathogenic bacterium in community-acquired pneumonia in the Japanese, 12 and the 23-valent pneumococcal polysaccharide vaccine has reduced the prevalence of pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Old age, underlying respiratory system disease, hypertension, hypercholesterolemia, heart disease, cerebral hemorrhage, cerebral infarction, stroke, diabetes mellitus, kidney disease, smoking, and low ADL status are associated with an increased risk of hospitalization due to pneumonia or influenza. 11 On the other hand, the vaccination rate typically is higher in healthy elderly than in weak elderly. Pneumococcus is cited as the major pathogenic bacterium in community-acquired pneumonia in the Japanese, 12 and the 23-valent pneumococcal polysaccharide vaccine has reduced the prevalence of pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear to be clinically relevant and plausible as, for example older patients are at higher risk of adverse outcomes from community acquired pneumonia [11]. Patients with previous smoking history are at risk of abnormal lung architecture, COPD and hence atypical bacterial infections [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review demonstrated that epilepsy, Parkinson disease, and multiple sclerosis were all risk factors for the development of community-acquired pneumonia, increasing risk by twofold to fourfold. 34 Neurologic disorders are believed to increase the risk of developing pneumococcal disease owing to a higher likelihood of aspiration. 2 As neurologic disorders were also independent predictors of mortality in this study, and considering the infection and potential mortality prevention afforded by pneumococcal vaccination, further studies assessing the impact of pneumococcal vaccination on outcomes in patients with a history of neurologic disorders are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia has been shown to increase risk of developing pneumococcal infection as well as increased disease severity, likely due to an increased risk of aspiration similar to neurologic disorders. 2,34,38 A retrospective study of more than 1,000 patients with a mean age of 64 years showed that dementia was an independent predictor of increased pneumococcal infection severity (OR=4.23, 95% CI=1.24, 14.4), but was not a significant predictor of mortality. 38 However, severe infection, which was assessed in the aforementioned study as well as in this study via invasive disease and intensive care unit treatment, was predictive of mortality.…”
Section: Discussionmentioning
confidence: 99%